Dunford-Pettis property of the product of some operators - Aqzzouz, B.; Aboutafail, O.; Elbour, A. (Methods of Functional Analysis and Topology, 2011)
We establish a sufficient condition under which the product of an order bounded almost Dunford-Pettis operator and an order weakly compact operator is Dunford-Pettis. And we derive some consequences.